IslamTAM: revising technology acceptance model from the Islamic perspective - Alyami, Mona; Hussin, Husnayati; Abdullah, Zainatul Shima (Design for Scientific Renaissance, 2019)
The Islamic religion is not just a sentimental doctrine isolated from reality, but an integrated way of human life and a method that explains all aspects of life as social behaviors. Around 700 years ago, Muslim's Imams and scholars as Ibn al-Qayyim and Ibn Taymiyyah have established their visions and perceptions of behaviors as Action Occurrence in their books and writings, from their deep understanding of Islam. Based on that, this conceptual paper aims to revise the Technology Acceptance Model (TAM) from the Islamic perspective and develop a framework called “Islamic Technology Acceptance Model” (IslamTAM). The framework focuses on "Thoughts and Ideas" as the origin of all the optional doings according to Ibn al-Qayyim's view. In addition, the model also focuses on the importance of the “Ability”, as Ibn Taymiyyah’s view, to moderate the relationship between “Intention to Use” and “Actual Usage”.